Abstract 094: Sudden Onset Dysphagia: A Symptom To Be Aware of During Code Strokes - Aysha Abeer; Wilson Rodriguez; Nicholas Schaper; Yoan Ganev; Gunjanpreet Kaur; Adam Awad; Brian Miremadi (Stroke: Vascular and Interventional Neurology)
Introduction Lateral medullary infarction (LMI) can present with dysphagia, dysphonia, dysarthria, vertigo, nausea, skew deviation, and ipsipulsion. Patients may also exhibit sensory loss and ipsilateral Horner’s syndrome. LMS often develops because of an acute infarct from the vertebral arteries or posterior inferior cerebellar arteries (PICA). The most common mechanism of stroke usually is atherothrombosis, followed by cardioembolic, dissection and embolic source of undetermined source (ESUS). While dysphagia often accompanies the constellation of LMS symptoms, it is rarely the first symptom and has only been reported in a few cases in the literature. In this report we describe the case of a man in his 40s with acute onset dysphagia as the presenting finding ahead of an LMS diagnosis. Methods The patient was identified in routine clinical practice. Results A man in his 40s with medical history of HTN, type 2 DM and polycystic kidney disease, presented with sudden‐onset dysphagia which started while he was drinking alcohol. Later he noticed that he was unable to keep his balance. His National Health Institute Stroke Scale was 4. Neurologic exam was pertinent for left‐sided miosis, ptosis, and dysmetria. Pinprick and temperature sensation were decreased on the right arm and leg. Facial sensation to light touch was diminished on the left. Brain MRI showed an acute infarct in the left lateral medulla (Figure A). CTA showed calcified atherosclerosis of the V4 segment of left vertebral artery (Figure B). Mechanism of ischemic stroke was artery to artery thromboembolism from the left V4 segment of vertebral artery. For secondary prevention, dual antiplatelet therapy, high intensity statin, and optimization of his risk factors were initiated. Conclusion This case report demonstrates that dysphagia can be the initial symptom of an acute ischemic stroke. Diagnosis and recognition of an atypical presentation of lateral medullary syndrome can pose a particular challenge especially in this era of “time is brain” but is of the utmost importance to facilitate good outcomes. Patients presenting with dysphagia who have risk factors for stroke and no other obvious etiology for their symptoms should be worked up for possible cerebrovascular etiology.